2012
DOI: 10.1044/sbi13.4.136
|View full text |Cite
|
Sign up to set email alerts
|

Workload Status of School-Based Speech-Language Pathologists in Texas

Abstract: In 1993, the American Speech-Language-Hearing Association (ASHA) recommended caseloads of 40 for speech-language pathologists (SLPs) practicing in the public schools, a recommendation that was not feasible for most school districts. In addition, new laws and policies substantially increased the paperwork, responsibilities, and time expenditures required of the school-based SLP. ASHA subsequently instigated extensive reviews of the problem and, in 2002, suggested that schools instead use a “workload analysis ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“… 31 In pediatric speech and language pathology, SWAPs can work across varying numbers of schools, with the majority working between 2 schools, compared with 12% working across 5 or more. 34 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 In pediatric speech and language pathology, SWAPs can work across varying numbers of schools, with the majority working between 2 schools, compared with 12% working across 5 or more. 34 …”
Section: Resultsmentioning
confidence: 99%
“…This study also showed that after some time had passed, their scope of practice was broadened to include the writing up of reports to be checked by registered practitioners. Another article 34 on SWAPs in speech and language pathology showed that SWAPs had a broad scope of practice, with the majority of their time spent on direct services to students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the dearth of literature on time-study tools in school social work, our team turned to the fields of speech-language pathology (SLP), occupational therapy, physical therapy, medicine, and nursing, all of whom have begun developing a literature analyzing the difference between "caseload" and "workload" (Armstrong et al, 2012;Cecere, Crandall, Dixon, Schefkind & Williams, 2015;Nishigori et al, 2015;Storfjell et al, 2015). This literature resonated with us, as we both saw the disconnect between our own stated caseload as SSWs and our actual workload.…”
Section: What We Know About How Ssw Spend Their Timementioning
confidence: 99%
“…This concern about time is commonly shared by other school related-service professionals (e.g. occupational therapists, physical therapists, speech/language pathologists), who also report having too little time to carry out their work (American Occupational Therapy Association, 2015;Armstrong, White, Moorer-Cook, & Gill, 2012;Cecere, Crandall, Dixon, Schefkind & Williams, 2015). Other related-service research literatures and policy briefs have started to develop a distinction between "caseload" (how many youth are on a regular schedule to be seen by the school related-services professional in weekly or monthly time increments) and "workload" (what actual time is required to serve those students outside of their regularly scheduled time).…”
Section: Introductionmentioning
confidence: 99%